FEATURES OF AN INCLUSIVE APPROACH IN PHYSICS EDUCATION, SAFETY REQUIREMENTS, AND ADAPTATION MECHANISMS - Ernazarov Abdurazzok Nizamiddinovich (Bright Mind Publishing, 2025)
This article highlights the specific aspects of teaching physics based on inclusive education, safety rules for students with special needs, and adaptation strategies. The importance of implementing an inclusive approach in physics education and the requirements for creating a safe environment for students with disabilities in laboratory classes are analyzed. Recommendations are also made on didactic materials, methods and tools used in adapting the lesson process, as well as the role and professional training of the teacher in inclusive education. The conclusions and recommendations presented provide practical suggestions for improving the quality of inclusive physics education.
Keywords: Inclusive education, students with special needs, physics laboratory, safety rules, adapted textbooks, didactic tools, teacher training.